Proceedings of the Seminar on Sourcing of Oil Palm Planting Materials for Local and Overseas Joint-Ventures, 22-23 July 1996, Hotel Villa, Subang Jaya - Seminar on Sourcing of Oil Palm Planting Materials for Local and Overseas Joint-Ventures (1996 : Subang Jaya, Malaysia); Rajanaidu, N.; Jalani Sukaimi ([Bandar Baru Bangi] : PORIM, 1999)
28